A Call for Caution in Use of Pertussis Vaccine Effectiveness Studies to Estimate Waning Immunity: A Canadian Immunization Research Network Study. (12th December 2020) - Crowcroft, Natasha S; Schwartz, Kevin L; Savage, Rachel D; Chen, Cynthia; Johnson, Caitlin; Li, Ye; Marchand-Austin, Alex; Bolotin, Shelly; Deeks, Shelley L; Jamieson, Frances B; Drews, Steven J; Russell, Margaret L; et al.
Abstract: Background: Vaccine effectiveness (VE) studies provide essential evidence on waning vaccine-derived immunity, a major threat to pertussis control. We evaluated how study design affects estimates by comparing 2 case-control studies conducted in Ontario, Canada. Methods: We compared results from a test-negative design (TND) with a frequency-matched design (FMD) case-control study using pertussis cases from 2005–2015. In the first study, we identified test-negative controls from the public health laboratory that diagnosed cases and, in the second, randomly selected controls from patients attending the same physicians that reported cases, frequency matched on age and year. We compared characteristics of cases and controls using standardized differences. Results: In both designs, VE estimates for the early years postimmunization were consistent with clinical trials (TND, 84%; FMD, 89% at 1–3 years postvaccination) but diverged as time since last vaccination increased (TND, 41%; FMD, 74% by 8 years postvaccination). Overall, we observed lower VE and faster waning in the TND than the FMD. In the TND but not FMD, controls differed from cases in important confounders, being younger, having more comorbidities, and higher healthcare use. Differences between the controls of each design were greater than differences between cases. TND controls were more likely to be unvaccinated or incompletely vaccinated than FMD controls ( P  < .001). Conclusions: The FMD adjusted better for healthcare-seeking behavior than the TND. Duration of protection from pertussis vaccines is unclear because estimates vary by study design. Caution should be exercised by experts, researchers, and decision makers when evaluating evidence on optimal timing of boosters. Abstract : Policymakers need evidence to guide decisions on what to do about waning pertussis vaccine effectiveness, but estimates of the speed of waning vary according to study design. Until methods are optimized, policymakers should exercise caution before modifying pertussis immunization programs.